Entre caminhos: um estudo sobre as consequências da modernidade no Quilombo dos Nogueira na Cidade de Montes Claros – Minas Gerais - Edmilson Mendes de Faria (2017)
Within this dissertation are treated the consequences of modernity in the self-declared quilombo (maroons) community of the Nogueira. Located in the city of Montes Claros, capital of the northern region of Minas Gerais, Brasil, its territory has been established by Florentino José Nogueira and his wife, known as Dona Clara. Initially situated in a rural area, over the years, the land was encompassed by an urban environment. Nowadays the territory of the quilombo is the target of a legal dispute between the Nogueira family and the neighboring battalion Military Police of Minas Gerais (PMMG), which is claiming the area for itself. Throughout the development of the research, which took place through ethnography and social mapping together with the community, it was possible to observe the social organization of the Nogueira, as well as the cultural roots that enunciate their ethnic, social and religious identity. The consequences of modernity, which directly influence the way of life, material reproduction, work and social organization of the community, were also observed, which, currently involved in the conflict that threatens the right to its territory, experiences the fear that the remaining community members of might impact its roots even more by the loss of its territory and restrictions on its cultural and religious manifestations.